2013
DOI: 10.1161/strokeaha.113.001059
|View full text |Cite
|
Sign up to set email alerts
|

Combined Approach to Lysis Utilizing Eptifibatide and Recombinant Tissue Plasminogen Activator in Acute Ischemic Stroke–Enhanced Regimen Stroke Trial

Abstract: Background and Purpose In a previous study, 0.3 and 0.45 mg/kg of intravenous recombinant tissue plasminogen activator (rt-PA) were safe when combined with eptifibatide 75 mcg/kg bolus and a 2-hour infusion (0.75 mcg/kg per minute). The Combined Approach to Lysis Utilizing Eptifibatide and rt-PA in Acute Ischemic Stroke–Enhanced Regimen (CLEAR-ER) trial sought to determine the safety of a higher-dose regimen and to establish evidence for a phase III trial. Methods CLEAR-ER was a multicenter, double-blind, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 13 publications
0
63
0
Order By: Relevance
“…[14] Subsequently, Combined Approach to Lysis Utilizing Eptifibatide and rt-PA in Acute Ischemic Stroke-Enhanced Regimen (CLEAR-ER) trial evaluated increased tPA dose (0.6 mg/kg, lower than standard tPA dose) in the combination therapy. [15] There was a reduction in the rate of symptomatic ICH in the combination arm compared to (14) Clear-ER trial (15) Gahn et al (16) Morris et al (17) NINDS trial (1) CT 69 101 13 5 -tPA 25 25 --168 Male CT -53 6 5 -tPA -13 --96 NIHSS at presentation CT 14 12 11 16 -tPA 10 17 --15 Base mRS 0-1 CT 61 85 ---tPA 25 18 --104 Time CT -Combination therapy, tPA -Tissue plasminogen activator, NIHSS -National institutes of health stroke scale the control standard tPA arm (OR, 0.15; 95% CI, 0.01-1.40; P = 0.053). There was also a trend towards improved functional outcome (mRS 0-1) at 3 months (OR, 1.74; 95% CI, 0.70-4.31; P = 0.23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Subsequently, Combined Approach to Lysis Utilizing Eptifibatide and rt-PA in Acute Ischemic Stroke-Enhanced Regimen (CLEAR-ER) trial evaluated increased tPA dose (0.6 mg/kg, lower than standard tPA dose) in the combination therapy. [15] There was a reduction in the rate of symptomatic ICH in the combination arm compared to (14) Clear-ER trial (15) Gahn et al (16) Morris et al (17) NINDS trial (1) CT 69 101 13 5 -tPA 25 25 --168 Male CT -53 6 5 -tPA -13 --96 NIHSS at presentation CT 14 12 11 16 -tPA 10 17 --15 Base mRS 0-1 CT 61 85 ---tPA 25 18 --104 Time CT -Combination therapy, tPA -Tissue plasminogen activator, NIHSS -National institutes of health stroke scale the control standard tPA arm (OR, 0.15; 95% CI, 0.01-1.40; P = 0.053). There was also a trend towards improved functional outcome (mRS 0-1) at 3 months (OR, 1.74; 95% CI, 0.70-4.31; P = 0.23).…”
Section: Discussionmentioning
confidence: 99%
“…There was also a trend towards improved functional outcome (mRS 0-1) at 3 months (OR, 1.74; 95% CI, 0.70-4.31; P = 0.23). [15] Few small non-randomized case series have also been published demonstrating safety and efficacy of combination therapy in acute stroke. [16,17] Results of our retrospective pooled analysis are in consensus with a recent study which reported an absolute risk reduction of 6% in a matched analysis comparing outcomes in the CLEAR-ER trial to the NINDS tPA trial.…”
Section: Discussionmentioning
confidence: 99%
“…More phase III RCTs are clearly required before these agents are approved (Jauch et al, 2013). The multicentre, double-blind, randomised phase II trial Combined Approach to Lysis Utilizing Eptifibatide and rtPA in Acute Ischemic Stroke-Enhanced Regimen trial (CLEAR-ER) (sponsored by the NIH/NINDS) indicates the safety (in terms of SICH incidence) and efficacy (mRS) of the combination of reduced-dose rtPA (0.6 mg/kg) and eptifibatide compared with full-dose alteplase (0.9 mg/kg) alone (Pancioli et al, 2013; see also the post hoc analysis using historical control data by Adeoye et al, 2015). This study can be regarded as hypothesis-generation, suggesting a phase III further investigation.…”
Section: Antiplatelet Therapymentioning
confidence: 99%
“…Several such strategies have been tested, including combination of a thrombolytic agent with aspirin [101], an anticoagulant (argatroban) [102,103] or a glycoprotein IIb/IIIa antagonist (eptifibatide) [104], combination of a thrombolytic agent with sonothrombolysis [52], the use of a new generation of thrombolytic agents such as tenecteplase [105] or lowering the dosage of alteplase. To date, only one Phase III trial has been completed, showing that early combined administration of intravenous aspirin and alteplase does not improve outcome but rather increases haemorrhagic complications [101].…”
Section: Enhanced Intravenous Thrombolysis In Acute Ischaemic Strokementioning
confidence: 99%
“…Data regarding the combinations of anticoagulants [102,103,107] or glycoprotein IIb/IIIa [104] antagonists are promising, but definitive evidence of their efficacy has not been provided.…”
Section: Enhanced Intravenous Thrombolysis In Acute Ischaemic Strokementioning
confidence: 99%